Efficiency and Economic Scale of the Batik Industry in Tarakan City - Devi, Charitin; Ariani; Ansar, Rudi (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2024)
This research aims to measure, analyze the efficiency and economic scale of Asian Batik, D'Erte Batik, Semandate Batik and Julak Batik. The data used is primary data from interviews. Based on the results of data processing using EMS, the efficiency of cotton batik is only produced by Batik D'Erte and Satin Batik by Batik Asia is 100% efficiency each. For Cotton Batik produced by Asian Batik, Semandat Batik, and Julak Batik were inefficient by 98.16%, 35.47%, and 28.00%. Meanwhile, satin batik produced by Batik D'Erte, Batik Semandat, and Julak Batik were inefficient by 77.09%, 14.16%, and 21.43%. Each batik producer that is inefficient in its batik production has an intensity value ranging from 0.05 to 1.23. For cotton batik, the largest difference is the input from Julak Batik of Rp. 11,150,846 and satin batik, the largest difference is also in Julak Batik with an input difference of Rp. 9,632,727 and output of Rp. 200,000. The value of the regression coefficient of the production activities of the four producers is 1.340362, which is increasing return to scale, meaning that the production activities carried out by batik producers are at an increased rate of increase in yield or if an addition is made to capital, raw materials or labor in production, it will increase output by 1.34%.